2022
DOI: 10.1103/physrevb.106.134403
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of Ca3Mn2xRuxO7(0<

Abstract: We here report on the study of the crystallographic and magnetic properties of layered perovskites Ca 3 Mn 2−x Ru x O 7 (x 0.9). We observe a solid solution between Mn and Ru atoms in the whole series and all samples present the same orthorhombic structure independently of the Ru content. Different magnetic structures, depending on the Ru content in the sample, have been determined using neutron powder diffraction. For low Ru doping (x 0.1), there is a dominant G-type antiferromagnetic ordering in the perovski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Studies on single crystals of the undoped compound indicate that this metamagnetic behaviour is due to a spin-flop transition of the moments from along the a-axis to along the b-c plane [29]. However, investigations on Ru-doped Ca 3 Mn 2 O 7 , where moments have re-oriented into the b-c, plane also demonstrate a change in slope of the M-H curve [24]. Thus, further investigations on single crystalline doped compounds would be required to uncover the nature of metamagnetism and its relationship with anisotropy in these compounds.…”
Section: Magnetization Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies on single crystals of the undoped compound indicate that this metamagnetic behaviour is due to a spin-flop transition of the moments from along the a-axis to along the b-c plane [29]. However, investigations on Ru-doped Ca 3 Mn 2 O 7 , where moments have re-oriented into the b-c, plane also demonstrate a change in slope of the M-H curve [24]. Thus, further investigations on single crystalline doped compounds would be required to uncover the nature of metamagnetism and its relationship with anisotropy in these compounds.…”
Section: Magnetization Studiesmentioning
confidence: 98%
“…Chen et al and Zhang et al have shown that co-substitution of Fe/Al and Nb at the Mn or Ti sites of Ca 3 (Mn/Ti) 2 O 7 leads to an enhancement in the ferroelectric polarization owing to increased oxygen octahedral distortions [22,23]. More recently, ruthenium doping at the Mn site of Ca 3 Ru x Mn 2−x O 7 (0.05 ⩽ x ⩽ 0.9) was investigated by Blasco et al [24]. They reported an intriguing finding that the spins aligning along the out-of-plane direction (along the long axis) in the undoped compound were observed to be aligned in-plane upon doping.…”
Section: Introductionmentioning
confidence: 99%